Continuity as advertising value - Vargas Bianchi, Lizardo (2022)
The present paper introduces the concept and convenience of managing brand advertising as a continuum over time, presenting this practice as a value or equity due to its direct relationship with the salience and familiarity levels the brand acquires as a consequence. The advertising continuum as equity is framed in researcher's A.S.C. Ehrenberg view on how advertising works, a view which it's core aspects are stated in the paper's first section.